Revisão taxonômica e variação geográfica do complexo Chironius quadricarinatus (Boie, 1827) (Serpentes, Colubridae) - Santos, Vinícius Sudré dos (2016)
Snakes of the genus Chironius Fitzinger, 1826 include 22 species of racers widespread in Central and South America. As expected for taxa with wide distributions, geographic variations of several Chironius populations are poorly understood, and some species complexes require urgent taxonomic revision. Chironius quadricarinatus is one of such taxa. Occurring in the Atlantic Forest, Cerrado and Chaco formations, these populations are subject to considerable environmental diversity, a fact that may lead to local differentiation. Based on coloration details of head and venter, the southestern populations of C. quadricarinatus (Chaco forests in Argentina and Paraguay) are recognized in the literature as distinct from those of the Cerrado and attributed to the subspecies C. q. maculoventris. Herein, we present a study on external morphology and hemipenial variations among the populations of C. quadricarinatus based on a sample of 555 specimens from several localities in Brazil, Argentina, Paraguay and one record from Bolivia. Our results corroborate the recognition of C. q. maculoventris as a full species, as indicated by previous studies lacking traditional revisionary approach. In addition, we provide evidences of local differentiation in populations from the setentrional Atlantic Forest (to the north of the Rio Doce, possibly restricted in the southern Bahia) reflected by segmental counts, hemipenial morphology and body proportions. Finally, we discuss our results in view diversification hypotheses in the Atlantic Forest already detected for other taxa by previous authors.